Analisis Tata Letak Produksi CNC Batik dengan Group Technology dan Particle Swarm Optimization - Fauzi, Rifqi; Hartanti, Sri; Safitri, Tari Hardiani; Rifai, Achmad Pratama; Saifurrahman, Anas (Go-Integratif : Jurnal Teknik Sistem dan Industri, 2023)
The production of batik experiences an increasing demand every year. This requires an improvement in both productivity and flexibility in the batik production process. Layout becomes one of the crucial factors in enhancing productivity and flexibility since it influences the material handling process. Well-designed facility layouts can improve the smoothness of material transfer operations, reducing material handling distances and, consequently, lowering material handling costs. This research aims to provide the best alternative layout. Several stages are carried out in this research, including classification to group cells based on part family, using the Rank Order Clustering (ROC) and Similarity Coefficient (SC) methods. Next, the calculation of the shortest transfer distance is conducted using Distance-Based Score Calculation, along with the use of Particle Swarm Optimization (PSO) to determine the department sequence. The research results show that the same cell grouping is achieved using both ROC and SC methods, with Cell 1 {Spray paint, proxy paint, Compressor, Welding, Grinding}, and Cell 2 CNC Milling and CNC Turning. Based on the distance traveled problem, it is found that the travel distance on the existing intuitive layout and the new suggested flow is 315.75 and 292.96, respectively. Therefore, by implementing group technology to implement cell manufacturing, it can provide a more effective and efficient material flow and Work In Process (WIP). Meanwhile, the results PSO yields a total minimum travel distance of 7,701.851 meters and a total material handling cost of Rp. 220 per meter, resulting in a total material handling cost of Rp 1,694,407.